2019
DOI: 10.1177/2050313x19841962
|View full text |Cite
|
Sign up to set email alerts
|

Chronic extensor hallucis longus tendon rupture treated with double-bundle autograft of extensor hallucis capsularis: A case report

Abstract: The extensor hallucis capsularis is an accessory extensor tendon with varied occurrence. Here, we present the case of a 40-year-old man with chronic extensor hallucis longus tendon rupture treated using extensor hallucis capsularis tendon as a double-bundle autograft. He had dropped a knife proximal to the right hallux metatarsophalangeal joint 4 months ago. Computed tomography revealed the presence of extensor hallucis capsularis, with its width and thickness, and the point of divergence from the extensor hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…For late reconstruction of the EHL tendon requiring lengthening, techniques have been described using EDL (1) , semitendinosus, gracilis, peroneal longus, plantaris tendon, and accessory extensor of the EHL tendon (4) , in addition to the possibility of using an allograft from a tissue bank.…”
Section: Discussionmentioning
confidence: 99%
“…For late reconstruction of the EHL tendon requiring lengthening, techniques have been described using EDL (1) , semitendinosus, gracilis, peroneal longus, plantaris tendon, and accessory extensor of the EHL tendon (4) , in addition to the possibility of using an allograft from a tissue bank.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that it can be used as a source of material during an autograft, as in the case of an additional extensor hallucis longus (EHL). Kurishige ( 2019 ) used the extensor hallucis capsularis (a type of additional EHL) in treating EHL rupture. The effectiveness was assessed 1 year after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness was assessed 1 year after the operation. Significant improvements in strength of the EHL, its activity, and foot stabilization were noted (Kurashige 2019 ). Of course, other muscles could have been used in such a case.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the TA, EHL tendon lacerations need to be repaired in the first three months of injury [3]. Kurashige et al [10] reported a case of chronic EHL tendon rupture diagnosed with magnetic resonance imaging. In their work, the authors described successful grafting with the use of an accessory extensor hallucis capsularis tendon.…”
Section: Discussionmentioning
confidence: 99%